2020
DOI: 10.22146/ijc.40921
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization and Controlled Release Formulation on Intercalated 2-Methyl-4-chlorophenoxy Acetic Acid-Graphite Oxide (MCPA-GO) Nanocomposite

Abstract: In this present work, herbicide named 2-methyl-4-chlorophenoxy acetic acid (MCPA) was intercalated into the graphite oxide through ion-exchange method to produce an MCPA-GO nanocomposite as an herbicide delivery system. The formation of MCPA-GO nanocomposite was confirmed by using PXRD, Fourier Transform Infrared Spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA), UV-Visible Spectroscopy and Accelerated Surface Area Surface (ASAP). As for PXRD pattern, there was increasing in the basal spacing of the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The peaks at 2926, 1730, 1446 and 1224 cm −1 are due to the stretching of —CH, COO—, —CH and C—O—C, respectively. FTIR spectra of sulfoxaflor and MCPA‐loaded granules revealed that peaks characteristic for MCPA appeared at 1730 and 804 cm −1 , corresponding to the characteristic peaks of COO— stretching vibration and C—Cl bending vibration, respectively 33,34 . Interactions between polymers that lead to the formation of a herbicide matrix did not occur during preparation of the pesticide‐loaded granules.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 2926, 1730, 1446 and 1224 cm −1 are due to the stretching of —CH, COO—, —CH and C—O—C, respectively. FTIR spectra of sulfoxaflor and MCPA‐loaded granules revealed that peaks characteristic for MCPA appeared at 1730 and 804 cm −1 , corresponding to the characteristic peaks of COO— stretching vibration and C—Cl bending vibration, respectively 33,34 . Interactions between polymers that lead to the formation of a herbicide matrix did not occur during preparation of the pesticide‐loaded granules.…”
Section: Resultsmentioning
confidence: 99%